2019
DOI: 10.1021/acs.est.9b04454
|View full text |Cite
|
Sign up to set email alerts
|

Thallium Sorption onto Manganese Oxides

Abstract: The sorption of thallium (Tl) onto manganese (Mn) oxides critically influences its environmental fate and geochemical cycling and is also of interest in water treatment. Combined quantitative and mechanistic understanding of Tl sorption onto Mn oxides, however, is limited. We investigated the uptake of dissolved Tl­(I) by environmentally relevant phyllo- and tectomanganates and used X-ray absorption spectroscopy to determine the oxidation state and local coordination of sorbed Tl. We show that extremely strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 75 publications
5
80
0
Order By: Relevance
“…In a recent study on the sorption of Tl onto various Mn oxides (Wick et al 2019), it has been shown that hexagonal vacancy-containing birnessite can sorb Tl by oxidation and complexation.…”
Section: Genetic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study on the sorption of Tl onto various Mn oxides (Wick et al 2019), it has been shown that hexagonal vacancy-containing birnessite can sorb Tl by oxidation and complexation.…”
Section: Genetic Implicationsmentioning
confidence: 99%
“…http://www.minsocam.org/ (e.g Bidoglio et al 1993;Peacock and Moon 2012;. Voegelin et al 2015, Cruz-Hernández et al 2019Wick et al 2019) Brookins (1988). considered that under oxidizing conditions, thallium oxides: Tl O, Tl O 3 and Tl O dominate the Eh-pH space in order with increasing Eh, and only under strongly acidic oxidizing conditions Tl 3+ appears.…”
mentioning
confidence: 99%
“…Since this reaction is pH-dependent, we have measured the average oxidation state (AOS) of birnessite over the whole investigated pH range (4)(5)(6)(7)(8). The AOS of samples reacted with BPA (25 µM) alone only slightly decreased from 3.98 to 3.90 (±0.02).…”
Section: Effect Of H 2 O 2 On the Oxidative Ability Of Birnessitementioning
confidence: 99%
“…2,3 As a result, birnessite-type manganese oxides play a significant role in controlling the cycles of several key nutrients as well as the fate and mobility of inorganic and organic contaminants. [4][5][6][7][8][9] Acid birnessite has been widely investigated because it is structurally similar to biogenic "natural" manganese oxides. [10][11][12][13] The birnessite reactivity is mainly affected by solution pH, surface properties and composition of MnO2 and structural characteristics of redox-active contaminants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation